Ecourt Application And Litigation In Perma Number 7 Of 2022 On Electronic Case And Trial Administration (PA Pasuruan Year 2022) - Randithia Permata, Nasaritha (Dinasti Research, 2024)
The birth of Supreme Court Regulation Number 7 of 2022 is expected to provide convenience for justice-seeking parties and answer three main issues, namely delay, affordability (access), and integrity in handling a case (integrity). The entire case registered in ecourt in 2022 at the PA Pasuruan is not directly proportional to the case processed through elitigation so that the goal for the community to get justice through an electronic trial is not in accordance with the principle of Justice, which is simple, fast and low cost. In this study using empirical laws that are descriptive qualitative using sociological juridical approach. The data source of this study is the primary data obtained from field studies and secondary data from the library. Data collection techniques of this study are observation, interviews, and documentation. Data analysis techniques in the form of data reduction, data presentation, data verification and conclusions. The results of this study are first, that ecourt and litigation in Pa Pasuruan in 2022 have been running, but not yet maximized. Second, the factors that affect the implementation of ecourt and e-litigation in PA Pasuruan in 2022 are the lack of literacy or understanding for judges, especially those who are senior and also to the community on the use of technology and information and the lack of socialization related to e-litigation to the community and law enforcement. Third, the efforts made by PA Pasuruan to increase the use of ecourt and litigation in the PA Pasuruan are to socialize the latest features issued by the Supreme Court, namely litigation carried out by conducting technology guidance, seminars, and social media that allow this information to be conveyed to the public.